Olfactory alterations in patients with multiple sclerosis - Jordy, Sergio Semeraro; Starzewski, Alberto, Junior; Macedo, Felipe André Basso; Manica, Gabriela Reginatto; Tilbery, Charles Peter; Carabetta, Eduardo Gregorin (Arquivos de Neuro-Psiquiatria, 2016)
This cross-sectional study involves 100 multiple sclerosis (MS) and 100 non-MS patients, under the age of 60 years old, with nasal obstruction, traumatic brain injury, previous rhinoplasty or neurosurgery, and so forth. Objective To assess olfactory function using the Connecticut test and verify correlations between olfactory alteration, disease duration and the Expanded Disability Status Scale (EDSS).Methods One hundred MS patients and 100 healthy control patients responded to a questionnaire. Those with olfactory alteration underwent a facial CT to exclude other causes.Results Thirty-two percent of patients showed alterations, compared with 3% in the healthy control group. Patients having EDSS above 4, showed a 5.2-times increased risk of dysfunction. Patients over 38 years of age have a 2.2-times increased risk over younger patients.Conclusions Because MS patients are likely to experience olfactory alterations, this study is a useful tool in follow-up care, although more studies are necessary to evaluate the correlations in MS evolution.
Keywords: multiple sclerosis; smell